(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This article delves into the realm of postcolonial literature, exploring its role in giving voice tonarratives of resistance and identity following the era of colonial rule. It examines the historical context ofpostcolonial literature, its significance in challenging dominant narratives, and its impact on the globalliterary landscape. The article investigates key themes and characteristics of postcolonial literature,including cultural hybridity, identity, resistance, language reclamation, and the experiences ofmarginalized groups. By analysing representative postcolonial works, it highlights how authors depictresistance against colonial oppression, reassert cultural identities, and engage with issues of genderand intersectionality. Furthermore, the article discusses the process of decolonizing literature andlanguage, acknowledging both challenges and opportunities. Through its exploration of these themes,the article underscores the lasting relevance of postcolonial literature in shaping global perspectivesand fostering cultural understanding.